2020
DOI: 10.1186/s13045-020-00946-7
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis, necroptosis, and pyroptosis in anticancer immunity

Abstract: In recent years, cancer immunotherapy based on immune checkpoint inhibitors (ICIs) has achieved considerable success in the clinic. However, ICIs are significantly limited by the fact that only one third of patients with most types of cancer respond to these agents. The induction of cell death mechanisms other than apoptosis has gradually emerged as a new cancer treatment strategy because most tumors harbor innate resistance to apoptosis. However, to date, the possibility of combining these two modalities has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
740
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 841 publications
(808 citation statements)
references
References 168 publications
6
740
0
1
Order By: Relevance
“…The most effective drugs currently used in the oncological field are, among others, the vinca alkaloids vincristine and vinblastine, etoposide, paclitaxel, topotecan, and irinotecan, which all originate from terrestrial plants [ 9 ]. Interestingly, although until a few years ago apoptosis was the anticancer mechanism of action described for these compounds, it has been shown that some of them also induce non-canonical cell deaths [ 10 , 11 ]. Many other different natural compounds were thus explored and identified as promoters of non-canonical cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective drugs currently used in the oncological field are, among others, the vinca alkaloids vincristine and vinblastine, etoposide, paclitaxel, topotecan, and irinotecan, which all originate from terrestrial plants [ 9 ]. Interestingly, although until a few years ago apoptosis was the anticancer mechanism of action described for these compounds, it has been shown that some of them also induce non-canonical cell deaths [ 10 , 11 ]. Many other different natural compounds were thus explored and identified as promoters of non-canonical cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis, pyroptosis, and ferroptosis are discussed in this review. These types of cell death are caused by membrane disruption induced by specific signal cascades [ 136 ], which can elicit an inflammatory response within the tumor tissue [ 137 ]. The induction of RNCD in tumor tissues does not necessarily lead to positive results in cancer patients, since the inflammatory response in the tissues can have favorable or adverse effect depending on the tumor type [ 138 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, cancer immunotherapy based on immune checkpoint inhibitors (ICIs) has achieved great success in basic medical research and clinical practice. However, ICIs are signi cantly limited by the fact that only one-third of patients with most types of cancer respond to these agents [43]. Tumor cells undergoing ferroptosis can trigger robust antitumor immunity in vivo and in vitro, and their e cacy can be synergistically improved by ICIs, even in ICI resistance.…”
Section: Discussionmentioning
confidence: 99%